2019
DOI: 10.3390/ijms20215288
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity Determination of Quaternary (Fluoro)Quinolones by Chromatographic and Theoretical Approaches

Abstract: Lipophilicity is a vital physicochemical parameter of a molecule, which affects several biological processes such as absorption, tissue distribution, and pharmacokinetic properties. In this study, evaluation of lipophilicities of a series of novel fluoroquinolone-Safirinium dye hybrids using chromatographic and computational methods is presented. Fluoroquinolone-Safirinium dye hybrids have been synthesized as new dual-acting hydrophilic antibacterial agents. Reversed phase thin-layer chromatography and micella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…Moreover, due to the presence of permanent positive charge within the triazolium moiety, Saf dyes were employed as ionization tags suitable for peptide identification [6]. chromatography (RPLC) and micellar electrokinetic chromatography (MEKC) [8]. The importance of drug candidate characterization in terms of their physicochemical properties is critical, since these analyses support selection of the most promising compounds [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the presence of permanent positive charge within the triazolium moiety, Saf dyes were employed as ionization tags suitable for peptide identification [6]. chromatography (RPLC) and micellar electrokinetic chromatography (MEKC) [8]. The importance of drug candidate characterization in terms of their physicochemical properties is critical, since these analyses support selection of the most promising compounds [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To study the possibility of using computer models to calculate LogP ow [ 21 ], miLogP ow values were calculated for the same substances by the Molinspiration package [ 22 ], which is an online tool available at . The method for logP prediction developed at Molinspiration (miLogP ow ) is based on group contributions.…”
Section: Methodsmentioning
confidence: 99%
“…Lipophilicity, defined as the affinity of a compound towards nonpolar phase, is also significant for potential drug evaluation [ 29 ]. The log P parameter is linked to the absorption, distribution, metabolism and excretion processes [ 30 , 31 ]. It has been shown that lipophilicity that is too high is associated with undesirable properties, such as accumulation of the compound in the adipose tissue [ 32 ].…”
Section: Introductionmentioning
confidence: 99%